2017
DOI: 10.1163/22244662-06301009
|View full text |Cite
|
Sign up to set email alerts
|

Diversity metrics, species turnovers and nestedness of bird assemblages in a deep karst sinkhole

Abstract: We reported a study on breeding birds occurring inside an 80 m-deep karst sinkhole, with the characterization of the assemblages recorded along its semi-vertical slopes from the upper edge until the bottom. The internal sides of the sinkhole have been vertically subdivided in four belts about 20 m high. The highest belt (at the upper edge of the cenote) showed the highest values in mean number of bird detections, mean and normalized species richness, and Shannon diversity index. The averaged values of number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Karst sinkholes are peculiar structures characterized by sudden changes in altitude, temperature, and lighting: these environmental gradients can influence some ecosystem components [1][2][3]. Among these components, birds are still little studied in these peculiar ecosystems [4,5]. This note reports data on the community structure of breeding birds in a deep karstic sinkhole located in central Italy (Pozzo del Merro; Latium), actively studied in the past decades regarding geology and vegetation [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karst sinkholes are peculiar structures characterized by sudden changes in altitude, temperature, and lighting: these environmental gradients can influence some ecosystem components [1][2][3]. Among these components, birds are still little studied in these peculiar ecosystems [4,5]. This note reports data on the community structure of breeding birds in a deep karstic sinkhole located in central Italy (Pozzo del Merro; Latium), actively studied in the past decades regarding geology and vegetation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report, for the first time, original data relating to the density of breeding (territorial) species within the sinkhole recorded with a mapping method: a census technique useful to obtain data at species and community level (species richness, diversity, and evenness). Furthermore, the results obtained were compared with the data obtained with the point counts method carried out in the same phenological period [4]. Although the mapping method obtains fine-grained data [7], it is time-consuming compared to the more rapid method of point counts [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the accumulation of cold-adapted plants (e.g., high montane and glacial relict species) within certain microhabitats of dolines -such as poleward-facing slopes and bottoms -is a prime indicator of the presence of current warm-stage microrefugia. Although recent investigations have indicated that dolines may also provide safe havens for various functional groups of animals from different phyla (Vilisics et al, 2011;Kemencei et al, 2014;Raschmanová et al, 2015Raschmanová et al, , 2018Růžička et al, 2016;Battisti et al, 2017;Bátori et al, 2019), data on many taxa is scarce or completely lacking. Furthermore, most of these studies do not provide information about the effects of habitat heterogeneity and related vegetation patterns on the functional diversity of animal assemblages within dolines.…”
Section: Introductionmentioning
confidence: 99%
“…Dolines provide steep gradients of environmental conditions (e.g., soil moisture and temperature) within very short distances (Whiteman et al 2004;Chauchard et al 2007;Su et al 2017), enabling them to facilitate the persistence of various functional groups of species in various phyla (Růžička et al 2016;Breg Valjavec et al 2018a;Bátori et al 2019). As a result, they are characterised by high genetic (Egli 1991;Su et al 2017), taxonomic (Bátori et al 2014b;Kemencei et al 2014;Raschmanová et al 2015;Růžička et al 2016;Battisti et al 2017) and microhabitat diversity (Özkan et al 2010;Bátori et al 2019) and may offer the best chances of survival for cool-adapted species and/or species retreating from global warming (i.e. trailing edge and stabilized relict populations) (Hampe and Petit 2005;Bauer 2018;Bátori et al 2019).…”
Section: Introductionmentioning
confidence: 99%